55 The Effectiveness of Model Think Pair Share to Social Science Learning Outcomes of Grade III Students of Primary Schools in Unit Of Ahmad Yani District of Boja Kendal Regency - Yuliastuti, Khanifah; Abbas, Nuraeni (Universitas Negeri Semarang, 2019)
The problem found in Elementary School Ahmad Yani cluster Kendal was the low learning achievement of IPS subject. This was caused by several aspects such as the less varied learning model, the inability of students to use their own knowledge, and lack of critical thinking in problem solving. Therefore, there is a need to provide innovative model to create more effective teaching and learning process. To answer such problem, this study used Quasi-Experimental research method with Nonequivalent Control Group Design. Through this design, the researchers involved all the third grade of Elementary School in Ahmad Yani Cluster Kendal as the population of this study. They were sampled by using cluster sampling. After the samples were obtained, the researchers decided experimental and control groups. They were as many as 28 students of SD 2 Campurejo involved as the experimental group, while 22 students of SD 2 Tampingan as the control group. In addition, the dependent variable of this study was Think Pair Share model, while the independent variable was IPS subject learning achievement with the topic of the history of currency. Their data were collected using observation, documentation and tests. Meanwhile, the hypotheses and effectiveness were examined by using t-test and gain test. The results of the study showed that Think Pair Share model was effective toward IPS subject learning achievement of the third grade students with the topic of the history of currency. Further, the posttest average score of experimental class was higher than control class. Also, the posttest mean of experimental group was 78.6 and the posttest mean of control group was 67.7. Moreover, the calculation of gain index showed that experimental class was on fair category with the score of 0.6180, while the control class achieved the criteria as many as 0.4055. At last, this study suggests that TPS model is better to use in any subjects in order to create innovative teaching and learning.